Changes in the Arctic Ocean Carbon Cycle With Diminishing Ice Cover. Issue 12 (13th June 2020) - DeGrandpre, Michael; Evans, Wiley; Timmermans, Mary‐Louise; Krishfield, Richard; Williams, Bill; Steele, Michael
Abstract: Less than three decades ago only a small fraction of the Arctic Ocean (AO) was ice free and then only for short periods. The ice cover kept sea surface p CO2 at levels lower relative to other ocean basins that have been exposed year round to ever increasing atmospheric levels. In this study, we evaluate sea surface p CO2 measurements collected over a 6‐year period along a fixed cruise track in the Canada Basin. The measurements show that mean p CO2 levels are significantly higher during low ice years. The p CO2 increase is likely driven by ocean surface heating and uptake of atmospheric CO2 with large interannual variability in the contributions of these processes. These findings suggest that increased ice‐free periods will further increase sea surface p CO2, reducing the Canada Basin's current role as a net sink of atmospheric CO2 . Plain Language Summary: The Arctic Ocean (AO) ice cover is decreasing, exposing the sea surface to exchange with the gases in the atmosphere. Consequently, anthropogenic CO2 that has accumulated in the atmosphere can now more readily enter the AO. It is expected that this will lead to an increase in CO2 in the AO but because of a lack of data in the region, a clear relationship has not been established. We have measured the partial pressure of CO2 ( p CO2 ) in the Canada Basin of the AO during five cruises spanning 2012–2017. These data have revealed that the p CO2 is higher during years when ice concentration is low, supporting the previous hypothesis. Using a model, we have shown that while uptake of atmospheric CO2 has increased p CO2, heating has also been important. These processes vary significantly from year to year, masking the likely increase in p CO2 over time. Based on these results, we can expect that while the Canada Basin has been a sink for atmospheric CO2, the uptake of atmospheric CO2 will diminish in the coming years. Key Points: The Arctic Ocean is losing ice cover at a rapid rate The loss of ice cover is leading to heating and uptake of atmospheric CO2, increasing sea surface CO2 levels Continued increase of sea surface CO2 will likely reduce the uptake of atmospheric CO2 in the future